Vital status in the National Panel Survey of Black Americans: a test of the National Death Index among African Americans. - LaVeist, T. A. (National Medical Association, 1996)
To test the specificity of the National Death Index (NDI), information was submitted on 157 randomly selected respondents from the National Panel Survey of Black Americans (NPSBA) who were known to be living as of 1992. Information also was submitted for 153 known deceased respondents from the panel survey to test the sensitivity of the NDI. The NDI was very sensitive; however, specificity was somewhat less impressive. Although we found the NDI/NPSBA match to be highly accurate, there was a nontrivial number of false positives.